A Comparative Kinetic Study of Acidic Hydrolysis of Wastes Cellulose from Agricultural Derived Biomass - Ajani AO; SE Agarry; OO Agbede (Journal of Applied Sciences and Environmental Management)
Bioconversion of agricultural waste products to produce value-added fuels and chemicals offers potential economical, environmental and strategic advantages over traditional fossil-based products. The kinetics of acid hydrolysis of cellulose isolated from banana skin, cowpea shells, maize stalks and rice husk (agricultural waste) were studied at temperature ranging between 70 – 100oC in a stirred conical flask which served as a batch reactor. The effect of acid concentration on cellulose hydrolysis was also investigated. The results showed that the rate of hydrolysis by virtue of glucose yield generally increased with increase in temperature and acid concentration for all the four agricultural wastes used. The experimental data were fitted to integrated first order rate kinetics and the results obtained suggested a first order rate of glucose formation from four agricultural wastes cellulose used. The activation energies estimated from Arrhenius equation are 39.60 KJ/mole, 38.83 KJ/mole, 44.37 KJ/mole and 34.29 KJ/mole for banana skin, cowpea shells, maize stalks and rice husk cellulose, respectively. These values suggests the ease with which hydrolysis can occur between the four agricultural wastes cellulose. @JASEM